Analisis Faktor yang Mempengaruhi Indeks Pembangunan Manusia di Kawasan Timur Indonesia - Jihan Githa Widianti; Rinaldi Rustam; Dini Hariyanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Human Development Index as a benchmark for the welfare of a country's resources. The Human Development Index is closely related to economic development. Indonesia as a country with human resources that are expected to meet the quality of superior human resources in terms of quantity and can compete in the era of globalization. This study aims to analyze the effect of the Education Budget, Health Budget, Regional Original Income, Village Funds, Poverty, Food Security, Income, Expected Years of Schooling, Average Years of Schooling on the Human Development Index in Eastern Indonesia in 2019-2023. This study took 63 Cities/Regencies in Eastern Indonesia Economic Development Region X. The results of the study stated that the variables Education Budget, Health Budget, and Average Years of Schooling had a positive and significant effect on the Human Development Index in Eastern Indonesia in 2019-2023. Meanwhile, the variables of Regional Original Income, Village Funds, Poverty, Food Security, Income, and Expected Years of Schooling gave insignificant results on the Human Development Index in Eastern Indonesia in 2019-2023. Through this study, it is hoped that Eastern Indonesia can further improve the Human Development Index for the welfare of the community.